2020
DOI: 10.3390/ijms21176241
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Adipose Tissue Browning as a Strategy to Combat Obesity

Abstract: The ongoing obesity pandemic generates a constant need to develop new therapeutic strategies to restore the energy balance. Therefore, the concept of activating brown adipose tissue (BAT) in order to increase energy expenditure has been revived. In mammals, two developmentally distinct types of brown adipocytes exist; the classical or constitutive BAT that arises during embryogenesis, and the beige adipose tissue that is recruited postnatally within white adipose tissue (WAT) in the process called browning. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
99
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(106 citation statements)
references
References 152 publications
1
99
0
6
Order By: Relevance
“…Mitochondria is rich in BAT, and the physiological function of it is recognized by non-trembling heat, moreover, mitochondrial biogenesis plays a crucial role in generating heat in brown fat ( 41 ). This in turn is regarded beneficial to improve obesity by activating brown fat to increase energy expenditure and white fat browning ( 42 ). Researchers have found that hypothalamus can stimulate eating and influence the expression of UCP-1 mRNA ( 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria is rich in BAT, and the physiological function of it is recognized by non-trembling heat, moreover, mitochondrial biogenesis plays a crucial role in generating heat in brown fat ( 41 ). This in turn is regarded beneficial to improve obesity by activating brown fat to increase energy expenditure and white fat browning ( 42 ). Researchers have found that hypothalamus can stimulate eating and influence the expression of UCP-1 mRNA ( 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to AMPK activation, HSL phosphorylation increased following TR 500 μ M administration ( p < 0.001) ( Figure 5(c) ). Intriguingly, the activatory phosphorylation of AMPK (Thr172) following TR treatment and the subsequent increase in ATGL-mediated lipolysis promote uncoupling protein 1 (UCP1) expression leading to the initial step of adipose tissue browning [ 36 ]. Accordingly, both TR 300 and 500 μ M enhanced the expression levels of UCP1 in fully differentiated 3T3-L1 ( p < 0.05 and p < 0.001, respectively) ( Figure 5(d) ), suggesting that TR administration may reduce adipogenesis by promoting adipose tissue browning.…”
Section: Resultsmentioning
confidence: 99%
“…There is now evidence for a third type of adipose tissue, beige adipose tissue, which has been found in WAT depots but is more energetically active like BAT [ 3 ]. The induction of beige adipocyte biogenesis or beiging in WAT depots and the activation of BAT is an attractive strategy to combat obesity [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cold exposure and exercise are methods by which BAT activation and beiging can be induced in humans [ 10 ]. A range of dietary compounds, including capsaicin, resveratrol, curcumin, green tea catechins, berberine, omega-3 polyunsaturated fatty acids and all-trans retinoic acid, have been examined in animals and humans as promoters of BAT thermogenesis and beiging with mixed results [ 4 ].…”
Section: Introductionmentioning
confidence: 99%